Nurses’ experiences in caring for dying patients: A literature review - Agus Ari Pratama; Shanti Wardaningsih (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Every human will face death, and some patients can experience a critical condition during illness before death. Nurses are medical professionals who are expected to be able to care for a patient's critical condition. Studying experiences of nurses in dealing with a patient's critical condition is needed so that they can improve their services. This study aims to analyze articles that explain about nurses' experiences in dealing with dying patients. A literature review was conducted by searching articles from the PubMed and EBSCO databases (using keywords "dying AND nurse AND experience"). In the PubMed databases were found 563 articles, and in the EBSCO were found 1,632 articles. From the all the databases, only 10 articles met the inclusion and exclusion criteria. Results of the article reviews found that the experiences of nurses in caring for dying patients suggest nurses to have more empathy and to provide contextual moral encouragement for patients and their families. Nurses also need to prepare themselves with knowledge about end of life.